Teaching Health Education Through the Development of Student Centered Video Assignment - Wallace, Heather; VanderMolen, Julia (Frontiers in Public Health, 2019)
Abstract: The purpose of this study was to explore the ways in which a student created video assignment enhanced student learning about developing and teaching a health education plan designed to address a complex public health problem. The objectives of the assignment included (1) to explore a complex public health problem, (2) practice developing a corresponding health education plan, and (3) develop and fully execute a multimedia video to deliver high impact health education and or promotion to a diverse audience. The assignment, referred to as the TED-Ed Video assignment was developed and piloted at Grand Valley State University and included students participating in a 200 level undergraduate introductory public health course as well as an undergraduate honors course on health and spirituality. Students working in groups of 3-4, worked through the project in multiple steps: problem identification, problem solving, plan development and the creation of the video, which included four primary elements: Watch, Think, Dig Deeper and Discuss. Upon completion of the video, students were asked to voluntarily complete a 10-question survey about the benefits of learning through a video creation assignment. A total of 15 students completed the survey with the majority either strongly agreeing or agreeing that the video assignment enhanced learning. Survey results suggest that the assignment is beneficial and favored over other assignment types. Additionally, students reported that the project was beneficial in learning the concepts and competencies associated with public health education. Finally, students indicated that the creation of videos as a means to explore and apply course concepts was favored as an assignment format in future coursework.